Correction: BRF1 accelerates prostate tumourigenesis and perturbs immune infiltration (Oncogene, (2020), 39, 8, (1797-1806), 10.1038/s41388-019-1106-X) - Loveridge C.J.; Slater S.; Campbell K.J.; Nam N.A.; Knight J.; Ahmad I.; Hedley A.; Lilla S.; Repiscak P.; Patel R.; Salji M.; Fleming J.; et al. (Springer Nature, 2024)
Indexed by Scopus/ERA